Classroom-based micro-sessions of functional high-intensity circuit training enhances functional strength but not cardiorespiratory fitness in school children: a feasibility study - Engel, Florian; Wagner, Matthias; Schelhorn, Franziska; Deubert, Felix; Leutzsch, Sascha; Stolz, Alexander; Sperlich, Billy (Frontiers in Public Health, 2019)
The present study assessed the short-term effect of 6-min classroom-based micro-sessions of multi-joint functional high-intensity circuit training (FunctionalHIIT) performed by students during regular classes on parameters related to functional strength and cardiorespiratory fitness. In this randomized controlled 4-wk study, 17 students (12 male; 5 female; age: 11.6±0.2 years) performed 6-min of FunctionalHIIT (targeting >17 on the Borg scale) four days per week during regular school classes and 18 students (12 male; 6 female; age: 11.7±0.3 years) served as control group (CG) without any additional in-class physical activity. The FunctionalHIIT group completed 86% of all planned sessions (mean duration: 6.0±1.5 min) with a mean RPE of 17.3±2.1. Body height, mass and BMI did not differ between the groups at baseline or between pre- and posttesting (p>.05; eta²≤.218). The performances in lateral jumping (p<.000; part eta²=.382; Δ% 4.6±8.6), sit-ups (p<.000; part eta²=.485; Δ% 3.1±8.6) and 20-m sprints (p<.000; part eta²=.691; Δ% 15.8±5.4) improved in both groups with greater increase following FunctionalHIIT. No baseline differences and no interaction effects occurred in performance of 6-min run, flexibility, push-ups, balance and long jump. Classroom-based FunctionalHIIT sessions, performed four days per week during four weeks did not improve variables related to aerobic endurance performance but enhanced certain parameters of functional strength in schoolchildren. As time is limited in the educational system of schools, FunctionalHIIT during regular school classes could offer a new perspective for increasing functional strength in schoolchildren.